Determinants of antihypertensive adherence among patients in Beijing: Application of the health belief model. Issue 11 (November 2016) - Yang, Shuaishuai; He, Chao; Zhang, Xuxi; Sun, Kaige; Wu, Shiyan; Sun, Xinying; Li, Yindong
Highlights: The antihypertensive adherence was not optimistic among adult patients in Beijing. Barriers and self-efficacy are important determinants of medication adherence. Self-efficacy is an important mediating variable. Abstract: Objectives: This study was aimed to determine the factors associated with antihypertensive adherence based on the Health Belief Model (HBM). Methods: A cross-sectional study was conducted in a rural area of China in 2014. The questionnaire included information about demographics, a scale based on the HBM, and the four-item Morisky Medication Adherence Scale. Results: 745 hypertensive patients participated in the study (345 men, 400 women). Patients' mean age was 56.4 ± 10.8 years. The prevalence of adherence was 43.5%. Structural equation modeling showed that men, older participants, and those with greater knowledge of hypertension showed better medication adherence than did other participants. Based on the HBM, higher levels of self-efficacy and perceived severity and a lower level of perceived barriers were associated with better antihypertensive adherence. Self-efficacy was one of the most important mediating variables affecting antihypertensive adherence. Conclusions: Antihypertensive adherence was not optimal among patients in Beijing. Given that many factors are associated with medication adherence, individualized intervention strategies should be carried out in Beijing, China, especially in community settings. Practice implications: Medication adherence can be improved by enhancing patients' self-efficacy because it was the most important influence and mediating variable.